Sensitive and Selective Chromatographic Method to Determine Vanadium in Commercial Phosphoric Acid - Hassan Pyar; Abdul Rahman Wahoud (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The spectrophotometric method adopting N-Benzoyl-N-phenylhydroxylamine was exechted for ascertaining vanadium in environmental samples. high performance liquid chromatography (HPLC) system equipped with a C18 RP column was used to determine vanadium in wet phosphoric acid and phosphate samples. A rapid pre-column response of vanadium with 5-Br-PADAP was used without prior separation or adding any masking agents. The results showed that, the chelates were detected after being injected through the column by UV- Vis detector at wavelength 585 nm. The molar absorptivity is 5.5 x104 and the retention time is 6.3 minutes. The sensitivity of this reagent is equal to twice as high as the use of (PAR) reagent. The RSD was 1.7% for weak concentrations to 0.22% for high concentrations and the relative error (RE) was between 3.21% and 1.07%. In conclusion the method of the currently study was found highly sensitive and selective and the results show a good accuracy and precision.